1998
DOI: 10.1103/physreva.58.2191
|View full text |Cite
|
Sign up to set email alerts
|

Multiple scattering effects on stopping power of large clusters in solids

Abstract: We study the effects on the electronic stopping power of large clusters in solids, resulting from multiple elastic scattering of each particle in the cluster by the target atoms, in the small-angle approximation. Evaluation of the cluster vicinage self-energy at the entrance of the target shows that large clusters may stabilize against the Coulomb explosion for a range of cluster sizes and speeds, so that the change of the cluster structure, due to multiple scattering, may have a noticeable influence on the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The droplet model shows that at least the main features of the cascade development can be explained without considering special coherent interactions of the cluster atoms when they move through the material or coherent effects such as Coulomb explosion in the cascade. [31][32][33][34] In the interaction model used in the simulations, the attractive interatomic forces depend solely on the approximated electronic density induced by the neighbor atoms without any excitations or electronic correlation effects. The short distance repulsive forces are calculated using the ZBL approximation, 14 which describes single ion collisions with a target.…”
Section: Validity Of the Modelmentioning
confidence: 99%
“…The droplet model shows that at least the main features of the cascade development can be explained without considering special coherent interactions of the cluster atoms when they move through the material or coherent effects such as Coulomb explosion in the cascade. [31][32][33][34] In the interaction model used in the simulations, the attractive interatomic forces depend solely on the approximated electronic density induced by the neighbor atoms without any excitations or electronic correlation effects. The short distance repulsive forces are calculated using the ZBL approximation, 14 which describes single ion collisions with a target.…”
Section: Validity Of the Modelmentioning
confidence: 99%
“…Generally, the stopping forces F s due to electron excitations in the target, the dynamically screened Coulomb interaction forces F int , and the random-deflection forces due to elastic multiple scattering at the target atoms all act simultaneously upon the individual carbon ions in the course of penetration. Compared with the other two forces, the multiple-scattering effect is not significant in the high-speed regime and can therefore be neglected in the present approach [8,17]. The equation of motion for the ith ion within the cluster is then given by…”
mentioning
confidence: 97%
“…For the sake of simulating multiple scattering, it is reasonable to assume that the cluster constituent ions are scattered independently from each other [10], and that each ion undergoes a random succession of binary collisions with the target atoms. We also assume that the multiple scattering is not affected by the variation of ion charge states in the course of penetration.…”
Section: Multiple Scatteringmentioning
confidence: 99%
“…Very recently, those authors have extended their early work by considering the multiple scattering on target atoms and the charge-state evolution of the cluster constituent ions [8]. On the other hand, calculations of the dynamically screened self-energy of fast C 60 clusters in solids showed that, owing to the wake pattern in the target dielectric response, the cluster structure could be stabilized against Coulomb explosion when the cluster size exceeds the characteristic length λ p = v/ω p , where v is the cluster speed and ω p is the plasma frequency of the electron gas in the target [9,10]. In a recent work, motivated by this conclusion, MD simulations were used to reveal strong asymmetries in Coulomb explosion patterns of fast C 60 clusters after long penetration times, which were attributed to the wake effects [11,12], showing that the use of Yukawa-type interaction potentials may have limited applicability in studies of Coulomb explosions in solids.…”
Section: Introductionmentioning
confidence: 99%